Managerial and Customer Costs of Price Adjustment: Direct Evidence from Industrial Markets - Mark Zbaracki; Mark Ritson; Daniel Levy; Shantanu Dutta; Mark Bergen (Bar-Ilan University, Department of Economics, 2003)
We study the price adjustment practices and provide quantitative measurement of the managerial and customer costs of price adjustment using data from a large U.S. industrial manufacturer and its customers. We find that price adjustment costs are a much more complex construct than the existing industrial organization or the macroeconomics literature recognizes. In addition to physical costs (“menu costs”), we identify and measure three types of managerial costs—information gathering, decision-making and communication costs, and two types of customer costs—communication, and negotiation costs. We find that the managerial costs are more than six times, and customer costs are more than twenty times, the menu costs. In total, the price adjustment costs comprise 1.22% of the company's revenue and 20.03 % of the company's net margin. We show that many components of the managerial and customer costs are convex, while the menu costs are not. We also document the link between price adjustment costs and price rigidity. Finally, we provide evidence of managers' fear of “antagonizing” customers.
Keywords: E12; E31; L16; F31; F41; 330; Menu cost; cost of price adjustment; managerial cost; customer cost; convex cost of price adjustment; sticky prices; price rigidity